2019
DOI: 10.1002/app.47801
|View full text |Cite
|
Sign up to set email alerts
|

Fire properties of carbon fiber reinforced polymer improved by coating nonwoven flame retardant mat for aerospace application

Abstract: In this study, two types of carbon fiber reinforced polymer (CFRP) flame retardant composites, CFRP@MatEG‐GF and CFRP@MatEG‐GF‐MW (EG, GF, and MW are the acronyms of expandable graphite, glass fiber and mineral wool, respectively), were prepared via compression molding, with expandable graphite‐based mat incorporated at the surface of the CFRP. The results showed that compared with the control CFRP, both CFRP@MatEG‐GF and CFRP@MatEG‐GF‐MW passed vertical burner test and 45° burner test according to FAR25.853. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 37 publications
0
21
0
Order By: Relevance
“…Carbon bre (CF) is one of the most valuable reinforcements for advanced composites due to its high specic strength, high specic modulus, low density and excellent thermophysical properties. [1][2][3] It has been widely used in the aerospace, automotive, sports and construction elds. [4][5][6] It is well documented that mechanical properties of CF composites are closely associated with the interface between the CF and resin matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon bre (CF) is one of the most valuable reinforcements for advanced composites due to its high specic strength, high specic modulus, low density and excellent thermophysical properties. [1][2][3] It has been widely used in the aerospace, automotive, sports and construction elds. [4][5][6] It is well documented that mechanical properties of CF composites are closely associated with the interface between the CF and resin matrix.…”
Section: Introductionmentioning
confidence: 99%
“…To fully apply composite materials in wide extent in aircraft vehicles, several drawbacks still need to be overcome, such as a suitable electrical conductivity to better cover several functions (e.g., lightning strike and electromagnetic compatibility issues) and continuous enhancement of fire safety in aviation materials. Many relevant achievements have been described in the literature in this direction [1,2,3,4,5,6,7,8,9,10]. Many functions can be conferred to aeronautical composites by proper use of nanotechnology, for example by embedding nanostructured materials with exceptional properties, like carbon nanotubes (CNTs), in aeronautical grade epoxy resins before or during the manufacturing processes [11,12,13,14,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated that the fire-retardant mat was effective as a barrier layer and the general mechanism of protection was that the expanded graphite formed a protective char. It was also observed that the EG tended to peel away from the mat, which may pose a health issue [ 19 ].…”
Section: Introductionmentioning
confidence: 99%